The reality of the implementation of national integrity standards in public sector by the council of common services of Irbid as perceived by the council staff - Daradkah, Sabrey Radi Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to reveal the council of common services of Irbid implementation of the national integrity standers in public sector, as perceived by the study community which they are the council staff, numbered of (63) employee including the first and second categories. To achieve the study objectives, a survey had been developed consists of 22 paragraphs, divided into 4 categories. First: rule of law, accountability second, transparency third, and good governance forth. After analysis the data, the results showed that the reality of the implementation of the national integrity standers by Irbid’s governance council of common services in the public sector as perceived by the council staff came at an average overall level and came to a low level in the area of good governance. The absence of statically significant differences (X=0.05) is attributable to the impact of the staff member’s category , with a value of 1.140 p and a stastical indication of 0.292. There are no statistically significant differences (X=0.05) attributable to the impact of the years of experience, with a value of 0.114 p and a statistical indication of 0.893. The result of the study showed that the absence of the job security of the end service comes first as the top hindrance with a rate of recurrence of (38) , and as a percentage of (%18.4) while (not working by the organizational structure ) , and (distinguishing between the employees) comes last with a rete of recurrence of (6) and as a percentage of (%2.9). Recommendations of the study: Work to amend personnel and administratively in line with the civil service system and remove distortions between them to achieve job security.